Formulation and Effectiveness Test of Centella Ethanol Extract (Centella asiatica (L) Urb) Serum as Skin Moisturizer - Nur Khairi,; Indrisari, Maulita; Rachman, Kiki (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2025)
Introduction: Indonesia has a tropical climate that tends to have high temperature and humidity, leaving skin dry and vulnerable to damage from sun exposure and pollution. One potential natural solution is the use of Centella asiatica extract, which is known to have skin hydration, regeneration, and protection effects. Aims: This study aims to develop a stable Pegagan ethanol extract-based serum formulation and evaluate its effectiveness as a skin moisturizer. Methods: Serum formulation with various concentrations of Pegagan extract (1%, 5%, and 10%), extracted using 70% ethanol through maceration method. The resulting serum was tested for physical and chemical stability, as well as its effectiveness in improving skin hydration using a skin analyzer on panelists with comparisons to anegative control (base formulation) and a positive control (brand X serum). Tests were conducted to observe the parameters of pH, viscosity, homogeneity, spreadability, adhesiveness, and effectiveness of skin hydration after product use. Result: The study showed that the serum with 1% extract concentration (F1) had the best stability, with stable viscosity and pH that is suitable for human skin (pH 5). Statistically, there were no significant changes before and after stability testing. Effectiveness testing using the skin analyser revealed a 30-50% improvement in skin hydration after 6 days of serum application, indicating that Formula F1 is effective in increasing skin moisture. Meanwhile, serums with higher extract concentrations (F2 and F3) showed decreased viscosity and instability. Conclusion: The 1% Centella asiatica extract-based serum was proven to effectively enhance skin hydration and may serve as a promising alternative skin moisturizer.